Human-Wildlife Conflict Management in Garhwal Himalayan Landscape: Present scenario, Issues, Challenges and Strategies - Singh Meena, Dharm; Pandey, Dheeraj; Patnaik, Sushant; Bisht, S.S.; Pundir, Devendra; Akash; Nupur (Indian Forester, 2022)
Human-wildlife conflict is an important issue in Uttarakhand for many decades. Severe loss incurred in terms of livestock predation, human injury, and death along with the crop raiding. Due to anthropogenic pressures on the wildlife habitats, large groups of wild animals are forced to occupy the multiuse landscapes outside the reserve forest areas. About 645 incidents have been recorded with a total of 740 casualties of livestock predation along with 126 incidents of human injured and 36 incident of human death in Narendranagar forest division between the periods of 2000 - 2020. Maximum attacks by wild animals were recorded when livestock was freely grazing without herder within the multi-use land. Leopard and elephant were mainly involved in human death whereas elephant and monkey in crop raiding. Present study also suggests supervised grazing, awareness of leopard prone areas, removing of unnecessary canopy of plants to reduce the conflicts cases in the study area. Further, the areas demand culturally and sustainable acceptable strategies to mitigate the damages and a comprehensive Human-Wildlife management plan should be formulated and implemented in each ranges of Narendranagar forest division.